The potential impact of the COVID-19 pandemic on child growth and development: a systematic review (2020)
Objective: This was a systematic review of studies that examined the impact of epidemics or social restriction on mental and developmental health in parents and children/adolescents. Source of data: The PubMed, WHO COVID-19, and SciELO databases were searched on March 15, 2020, and on April 25, 2020, filtering for children (0---18 years) and humans. Synthesis of data: The tools used to mitigate the threat of a pandemic such as COVID-19 may very well threaten child growth and development. These tools ---- such as social restrictions, shutdowns, and school closures ---- contribute to stress in parents and children and can become risk factors that threaten child growth and development and may compromise the Sustainable Development Goals. The studies reviewed suggest that epidemics can lead to high levels of stress in parents and children, which begin with concerns about children becoming infected. These studies describe several potential mental and emotional consequences of epidemics such as COVID-19, H1N1, AIDS, and Ebola: severe anxiety or depression among parents and acute stress disorder, post-traumatic stress, anxiety disorders, and depression among children. These data can be related to adverse childhood experiences and elevated risk of toxic stress. The more adverse experiences, the greater the risk of developmental delays and health problems in adulthood, such as cognitive impairment, substance abuse, depression, and non-communicable diseases. Conclusion: Information about the impact of epidemics on parents and children is relevant to policy makers to aid them in developing strategies to help families cope with epidemic/pandemic-driven adversity and ensure their children’s healthy development.